Pelatihan Public Speaking untuk Meningkatkan Kepercayaan Diri Siswa SMPN 4 Amarasi Selatan - Theresia Blandina Uge; Onesmius Valentino Jerubu; Indriyati Indriyati; Yasinta Palan Peten; Elisabeth Date Masan Welin (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The low public speaking skills among students at SMP Negeri 4 Amarasi Selatan prompted the implementation of public speaking training as a means of developing student skills and character. Observations showed that most students lacked confidence in public speaking and were less active in activities such as inter-school debates and other academic and non-academic activities. This training aimed to increase students' self-confidence and communication skills through the development of soft skills, particularly in public speaking. The training methods included lectures, discussions, simulations, and hands-on practice, conducted over a one-day period at the school. The results showed significant improvements in speaking skills, mastery of material, and effective use of body language. Based on the final evaluation, there was a significant increase in participants' self-confidence and communication skills. This activity had a positive impact on student character development and is recommended for ongoing implementation.